2023
DOI: 10.1002/sae2.12042
|View full text |Cite
|
Sign up to set email alerts
|

No rest for resting spores: Can predators mitigate clubroot disease?

Abstract: The clubroot pathogen Plasmodiophora brassicae is a major and growing problem for the cultivation of Brassica crops. As conventional control disease management methods are ineffective or prohibited due to their ecological impact, and crop resistance is frequently broken, biological control of the pathogen has become a key focus for the development of sustainable agricultural systems. Here we provide a perspective review on the unexplored impact of soil microbiome predators, and their potential use as biocontro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
1
0
Order By: Relevance
“…Living organisms in the soil, the rhizobiome and microbiome predators such as other protists, nematodes and arthropods can all influence the survival and therefore establishment and efficacy of biocontrol microorganisms against clubroot through competition, antibiosis or predation. So far, hardly anything is known about this complex topic in regard to clubroot, yet a recent study showed nonspecific consumption of P. brassicae resting spores by other protists (Schwelm et al, 2023).…”
Section: The Role Of Soil Properties and Microbiomesmentioning
confidence: 99%
“…Living organisms in the soil, the rhizobiome and microbiome predators such as other protists, nematodes and arthropods can all influence the survival and therefore establishment and efficacy of biocontrol microorganisms against clubroot through competition, antibiosis or predation. So far, hardly anything is known about this complex topic in regard to clubroot, yet a recent study showed nonspecific consumption of P. brassicae resting spores by other protists (Schwelm et al, 2023).…”
Section: The Role Of Soil Properties and Microbiomesmentioning
confidence: 99%
“…Through predation, microbiome predators release the nutrients inside their prey (nitrogen, phosphorus, or silica) or enhance prey activity to mobilize these nutrients (Jiang et al, 2023; Puppe, 2020; Ranoarisoa et al, 2020), which then become available and increase plant growth (Figure 1; Thakur & Geisen, 2019). Microbiome predators might also promote pathogen‐suppressive microorganisms via changes in the community composition (Gao et al, 2019; Guo et al, 2022; Thakur & Geisen, 2019) and feed on plant pests and pathogens, thereby reducing plant diseases (Figure 1; Geisen et al, 2016; Schwelm et al, 2023). Additionally, microbiome predators play a role in carbon cycling, by enhancing litter decomposition (Figure 1).…”
Section: What Is the Role Of Microbiome Predators In Soil Functioning?mentioning
confidence: 99%